Extractive foraging on hard‐shelled walnuts and variation of feeding techniques in wild Japanese macaques (Macaca fuscata) - Tamura, Masaya (American journal of primatology, 2020)
Extractive foraging is considered a key selective pressure for the evolution of primate cognitive abilities—the extractive foraging hypothesis. Although tool‐use and substrate‐use are representatives of the foraging strategy, some primates engage in extractive foraging without external objects. Manual processing skills of prickly foods have been described in some species, whereas there are few studies on other type of food defenses. Here, I describe extractive foraging of hard‐shelled walnuts by wild Japanese macaques (Macaca fuscata), focusing on whether they accomplish the tasks only by their physical strength or require manual and/or oral processing skills to crack open the walnut shells. The study subjects comprised all members of troop B1 and three nontroop males in Kinkazan Island, Japan. Walnut feeding was observed during the main walnut seasons (September–December) when the troop visited walnut patches for 79 days in 2 years. I categorized the walnut feeding behavior into complete cracking and partial cracking. The number of times the five behavioral elements in the cracking stage occurred were counted from complete cracking. All six adult males and 11 of the 17 adult/adolescent females showed complete cracking, while the remaining females were never observed exhibiting this activity, despite their physical maturity. I observed four clearly distinguishable cracking methods during walnut feeding in the 17 subjects. The compositions of five behavioral elements were different in each method. These results suggest that walnut feeding by Japanese macaques is not only by brute force but requires the acquisition of at least one of four cracking methods for the achievement of complete cracking. In particular, females need to compensate for their physical inferiority by increasing walnut manipulations. To my knowledge, this is the first detailed description on feeding techniques in primates to overcome hard‐shelled obstacles without the use of tools and even substrates. Illustrations and photographs of walnuts being processed with four cracking methods. (a) crunch, (b) bilateral‐crack, (c) unilateral‐crack, and (d) hole‐punch. Photos accompanying crunch are from video footage. Other photos are of feeding traces when monkeys gave up feeding. Black areas in the illustrations indicate cracked parts of the shell. Small arrows on the walnuts indicate directions of cracking. Research Highlights Wild Japanese macaques in Kinkazan Island required not only physical strength but also some feeding techniques for achieving hard‐shelled walnut feeding tasks. The monkeys showed four clearly distinguishable cracking methods during the tasks.